PRO-ACTIVE LEGISLATIVE TARGETS 1990 . PRO-ACTIVE PROPOSAL. NEW YORK HIRING DISCRIMINATION. (Tufts Archival Research Center, 2007)
Tobacco Institute report on New York legislation regarding hiring discrimination, advertising revenue maximization, and small business exemption from smoking law. Summarizes legislative action. Discusses industry action in terms of resources needed, economic analysis, expert witnesses, coalition allies, media, and grassroots mobilization.